Sintered alloy, method for manufacturing the same, and metal mold

By using the sintered bond between the compound phase and the Cr3C2 phase of NaCl type structure, the problem of mismatch of thermal expansion coefficients when forming the chalcogenide glass lens is solved, excellent oxidation resistance and mirror properties are achieved, and the mold life is extended .

CN117904508BActive Publication Date: 2025-02-07FUJI DIE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410249818.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-03-08
Filing Date
2024-03-05
Publication Date
2025-02-07
Estimated Expiration
2044-03-05

AI Technical Summary

Technical Problem

When forming chalcogenide glass lenses, existing metal molds are prone to problems due to mismatch in thermal expansion coefficients, and it is difficult to maintain mirror properties and oxidation resistance for a long time.

Method used

The sintered gold containing the compound phase and the Cr3C2 phase has a NaCl-type structure, including metal elements such as Nb, Ta, Ti, and C, and N, and the content is between 13 and 37% by volume, and is prepared by a hot pressing sintering process. .

Benefits of technology

It realizes excellent oxidation resistance and mirror properties of sintered bonded gold, extends the life of the metal mold, and is suitable for high thermal expansion coefficient materials such as molded chalcogenide glass lenses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117904508B_ABST
    Figure CN117904508B_ABST
Patent Text Reader

Abstract

A sintered alloy, characterized in that it includes a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80% by volume has a NaCl type structure, and the solid solution phase includes: one or more metal elements among Nb, Ta and Ti; one or more of W and Mo; and one or more of C and N. The sintered alloy contains 13 to 37% by volume of the compound phase, and 0.1 to 45 atomic % of one or more of W and Mo are solid-dissolved in the compound phase relative to the total amount of metal elements in the compound phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sintered alloy, a manufacturing method thereof and a metal mold. Background Art

[0002] SUS420J2, ultrafine cemented carbide, binderless cemented carbide, etc. are used as materials for metal molds for various optical lens molding. However, when shape accuracy is required for metal molds such as aspherical lenses, binderless cemented carbide with a small thermal expansion coefficient is used.

[0003] On the other hand, lenses used in infrared sensors or infrared thermal imagers are required to be lenses that easily transmit mid- to far-infrared rays (hereinafter referred to as "infrared lenses"). Existing infrared lenses have a glass transition temperature of 700°C or higher, making them difficult to mold using metal molds. Currently, chalcogenide glass lenses with a glass transition temperature of less than 500°C are provided.

[0004] Chalcogenide glass has a thermal expansion coefficient as high as 15.0 to 25.0 MK -1 Therefore, if the thermal expansion coefficient is 4.7~5.1MK -1 Therefore, in order to solve the problem during molding, Japanese Patent No. 5770357 proposes a metal mold using a Cr3C2-Ti(C,N)-VC-Ni alloy with a larger thermal expansion coefficient than that of binderless cemented carbide and a smaller difference in thermal expansion coefficient between the lens material and the mold.

[0005] However, in the metal mold formed by Cr3C2-Ti(C,N)-VC-Ni alloy, Ti(C,N) is sometimes fragile, and it takes time to finish the mirror surface of the metal mold. Therefore, Japanese Patent No. 6049978 invented a Cr3C2-NbC-Ni alloy, which also has a small difference in thermal expansion coefficient with the lens material, so it is difficult to cause problems during lens molding. In addition, NbC with a lower hardness than Ti(C,N) is used to easily obtain mirror properties.

[0006] These alloys are materials with better oxidation resistance than binderless cemented carbide. Recently, in order to increase the number of times that lenses can be molded, a material that can maintain the mirror surface of the metal mold for a longer period of time is needed. In addition, since the operating temperature may exceed 800°C, oxidation resistance is even more important. In addition, it is not limited to lens materials with a large thermal expansion coefficient. Even ordinary lens materials can be molded without problems using metal molds with a large thermal expansion coefficient according to the shape of the lens. In addition, it is not limited to metal molds for molding chalcogenide glass lenses, but also metal molds, components and tools for molding parts with excellent mirror surface, excellent high wear resistance and oxidation resistance. Summary of the invention

[0007] Problems to be solved by the invention

[0008] Therefore, an object of the present invention is to obtain a sintered alloy having excellent oxidation resistance and mirror finish and capable of extending the life of a metal mold.

[0009] Means of solving the problem

[0010] That is, the sintered alloy of the first embodiment of the present invention is characterized in that it includes a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80 volume % has a NaCl type structure, and the solid solution phase includes: one or more metal elements among Nb, Ta and Ti; one or more of W and Mo; and one or more of C and N. The sintered alloy contains 13 to 37 volume % of the compound phase, and 0.1 to 45 atomic % of one or more of W and Mo are solid dissolved in the compound phase relative to the total amount of metal elements in the compound phase.

[0011] The sintered alloy of the second embodiment of the present invention is characterized in that it contains a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80 volume % has a NaCl type structure, and the solid solution phase contains: metal elements of Ta and Nb and / or Ti; and one or more of C and N, and the sintered alloy contains 13 to 37 volume % of the compound phase.

[0012] The sintered alloy of the third embodiment of the present invention is characterized in that it contains a compound phase and a Cr3C2 phase, wherein the compound phase contains: Ta; and one or more of C and N, and more than 80 volume % has a NaCl type structure, and the sintered alloy contains 13 to 37 volume % of the compound phase.

[0013] The sintered alloy of the fourth embodiment of the present invention is characterized in that it contains a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80 volume % has a NaCl type structure, and the solid solution phase contains: metal elements of Nb and Ti; and one or more of C and N, and the sintered alloy contains 13 to 37 volume % of the compound phase.

[0014] The sintered alloy of the fifth embodiment of the present invention is characterized in that it contains a compound phase and a Cr3C2 phase, wherein the compound phase contains: Nb; and C and N, and more than 80 volume % has a NaCl type structure, and the sintered alloy contains 13 to 37 volume % of the compound phase.

[0015] The sintered alloy of the sixth embodiment of the present invention is characterized in that it includes a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase forms a solid solution phase, and more than 80 volume % has a NaCl type structure, the solid solution phase includes: one or more metal elements among Nb, Ta and Ti; one or more of W and Mo; and one or more of C and N, the metal phase includes one or more of Ni, Co and Fe, the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase, and in the compound phase, 0.1 to 45 atomic % of one or more of W and Mo are solid-dissolved relative to the total amount of metal elements in the compound phase.

[0016] The sintered alloy of the seventh embodiment of the present invention is characterized in that it includes a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase forms a solid solution phase, and more than 80 volume % has a NaCl type structure, the solid solution phase includes: metal elements of Ta and Nb and / or Ti; and one or more of C and N, the metal phase includes one or more of Ni, Co and Fe, and the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase.

[0017] The sintered alloy of the eighth embodiment of the present invention is characterized in that it includes a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase includes Ta, and one or more of C and N, and more than 80 volume % has a NaCl type structure, the metal phase includes one or more of Ni, Co and Fe, and the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase.

[0018] The sintered alloy of the ninth embodiment of the present invention is characterized in that it includes a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase forms a solid solution phase, and more than 80 volume % has a NaCl type structure, and the solid solution phase includes: metal elements of Nb and Ti; and one or more of C and N, and the metal phase includes one or more of Ni, Co and Fe, and the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase.

[0019] The sintered alloy of the tenth embodiment of the present invention is characterized in that it includes a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase includes Nb, C and N, and more than 80 volume % has a NaCl type structure, the metal phase includes one or more of Ni, Co and Fe, and the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase.

[0020] Preferably, the particle size of the compound phase is 0.1 to 6 μm.

[0021] The metal mold of the present invention is characterized by comprising any one of the above-mentioned sintered alloys.

[0022] The method for manufacturing a sintered alloy according to the first embodiment of the present invention is characterized in that it is a method for manufacturing the following sintered alloy, wherein the sintered alloy comprises a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and 80% by volume or more has a NaCl type structure, wherein the solid solution phase comprises: one or more metal elements selected from Nb, Ta and Ti; and one or more selected from C and N,

[0023] Containing 13 to 37% by volume of the compound phase,

[0024] The raw material powder is molded and the obtained molded body is sintered by hot pressing.

[0025] A method for manufacturing a sintered alloy according to a second embodiment of the present invention is characterized in that it is a method for manufacturing the following sintered alloy, wherein the sintered alloy comprises a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase forms a solid solution phase, and more than 80% by volume has a NaCl type structure, wherein the solid solution phase comprises: one or more metal elements selected from Nb, Ta, and Ti; and one or more selected from C and N, wherein the metal phase comprises one or more selected from Ni, Co, and Fe,

[0026] Containing 13 to 37% by volume of the compound phase,

[0027] The content of the metal phase is less than 0.5 volume %,

[0028] The raw material powder is molded and the obtained molded body is sintered by hot pressing.

[0029] The hot pressing is preferably performed in a vacuum or in an inert gas atmosphere at a pressure of 20 to 100 MPa and a sintering temperature of 1200 to 1500°C.

[0030] Effects of the Invention

[0031] According to the present invention, a sintered alloy having excellent oxidation resistance and mirror surface properties and capable of extending the life of a metal mold, a method for manufacturing the same, and a metal mold can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM photograph showing an example of the cross-sectional SEM structure of the sintered alloy of the present invention. DETAILED DESCRIPTION

[0033] A sintered alloy according to one embodiment of the present invention is characterized in that it comprises a compound phase MC and a Cr3C2 phase, wherein the compound phase MC comprises: one or more metal elements selected from Nb, Ta and Ti; and one or more selected from C and N, and has a NaCl type structure.

[0034] The compound phase MC is a carbide, carbonitride, nitride, or solid solution of Ti, Ta, and Nb, and has a NaCl-type structure. In this way, by using a compound phase MC containing any one of Ti, Ta, and Nb and having a NaCl-type structure as the main component, the oxidation resistance of the sintered alloy is improved. The compound phase MC may also contain one or more of Ti, Ta, and Nb. In particular, excellent oxidation resistance can be obtained by including Ti in the compound phase MC. The compound phase MC may also be a solid solution phase containing Ti in addition to Ta or Nb. In this case, the content of Ti is preferably 10 to 90 mol%, more preferably 40 to 80 mol%, relative to the amount of metal elements contained in the compound phase MC. The compound phase MC is preferably a carbide or a carbonitride. Among Ti, Ta, and Nb, because the hardness of Ti carbide is high, when there is more Ti in the compound phase MC, although it will become a material with excellent wear resistance, it also tends to be hard and brittle, so there is a situation where it is difficult to obtain mirror properties. In this case, the amount of Ti added can be a small amount. In addition, when it is desired to prevent the components of Ti, Ta and Nb from being mixed into the processed material, the amount of these elements can be reduced and adjusted. In addition, oxygen and boron may be contained, and the oxide or boride may be used.

[0035] The compound phase MC may contain only Ta as a metal element, or may be a solid solution phase containing Ta in addition to Nb and / or Ti. Thus, a sintered alloy having a high thermal expansion coefficient, high wear resistance, and excellent oxidation resistance can be obtained.

[0036] The compound phase MC may contain only Nb as a metal element and may contain C and N. By using Nb carbonitride as the compound phase, a NaCl type structure is easily formed, and a sintered alloy having excellent oxidation resistance while maintaining a desired thermal expansion coefficient can be obtained. The compound phase MC may be a solid solution phase containing Nb and Ti as metal elements. By making the compound phase MC a solid solution phase containing Ti in addition to Nb, particularly excellent oxidation resistance can be obtained.

[0037] It is preferred to contain 13 to 37% by volume of the compound phase MC. When the compound phase MC is less than 13% by volume, the Cr3C2 phase is prone to grain growth, so sufficient strength cannot be obtained. When the compound phase MC is more than 37% by volume, it is difficult to obtain mirror finish because the compound phase MC is harder and more brittle than the Cr3C2 phase. In addition, there is a tendency for the thermal expansion coefficient to be small because the content of the Cr3C2 phase is reduced. The content of the compound phase MC is more preferably 20 to 35% by volume.

[0038] In the compound phase MC, it is preferred to solid-dissolve one or more of W and Mo at 0.1 to 45 atomic % relative to the total amount of metal elements in the compound phase MC. WC and Mo2C have a hexagonal crystal structure when they are monomers, but when solid-dissolved in the compound phase MC, they can suppress the grain growth of the compound phase (hard phase) while maintaining the NaCl type crystal structure, and further improve the oxidation resistance of the sintered alloy. At this time, by changing the content of W and Mo, the rigidity and hardness of the sintered alloy can be changed, so the composition that makes the sintered alloy obtain the desired rigidity can be selected according to the purpose, and the hardness of the sintered alloy can be changed, thereby adjusting the mirror surface processing degree and wear resistance. In order to maintain the NaCl type crystal structure and improve the oxidation resistance, a small amount of W and Mo of about 0.1 to 43 atomic % can be solid-dissolved. If the balance between rigidity and hardness is considered, it is more preferred to solid-dissolve one or more of W and Mo at 5 to 40 atomic % relative to the total amount of metal elements in the compound phase MC, and it is further preferred to solid-dissolve 10 to 35 atomic %.

[0039] Here, the so-called compound phase MC has a NaCl type crystal structure, which means that in the alloy structure, among the compound phases other than the Cr compound phase, more than 80% by volume has a NaCl type crystal structure. That is, in addition to the NaCl type crystal structure, a small amount of crystals, oxides, borides, etc. having a hexagonal crystal structure may also be included. When the compound phase MC contains multiple metal elements, in addition to the solid solution having the NaCl type crystal structure, a hard phase having a core-shell structure may also be included. In addition, the compound phase MC may also be composed of multiple phases with different compositions.

[0040] Cr3C2 phase has 10.3MK -1The sintered alloy has a high thermal expansion coefficient and a hardness of nearly 1300 HV. Therefore, by using the Cr3C2 phase as the main component, the thermal expansion coefficient of the sintered alloy becomes higher, mirror finishing is easier, and the mirror surface property is improved. In addition, the sintered alloy uses the Cr3C2 phase as the main component and does not contain a hard phase other than the compound phase MC of the NaCl type structure with excellent oxidation resistance, so a synergistic effect of maintaining a more excellent mirror surface property for a long time can be achieved.

[0041] It cannot form Cr3C2 phase, but forms Cr 23 When the phase contains chromium compounds other than Cr3C2, such as C6 phase or Cr7C3 phase, the thermal expansion coefficient decreases in proportion to its content. In addition, since it is more fragile than Cr3C2, it is easy to cause problems as a tool. 23 A small amount of chromium compounds other than Cr3C2 such as C6 and Cr7C3 may be included. Here, the so-called "Cr3C2 phase" means that more than 80 volume % of the chromium compounds are Cr3C2 phase.

[0042] The atomic ratio of the amount of light elements such as C and N contained in the compound phase MC to the amount of metal elements contained in the compound phase MC is preferably greater than 0.8. If the atomic ratio of the light element amount is less than 0.8, the sintered alloy cannot be fully densified. In addition, if the ratio is small, compound phases other than the compound phase MC of the Cr3C2 phase and the NaCl type structure are easily generated, and high oxidation resistance cannot be obtained. The atomic ratio of the metal element to the light element is obtained as follows: the carbon amount of the Cr3C2 phase estimated based on the carbon amount of the Cr3C2 raw material powder used and the addition ratio is subtracted from the alloy carbon amount of the sintered body, and the atomic ratio is calculated based on the remaining components. The atomic ratio of the amount of light elements such as C and N contained in the compound phase MC to the amount of metal elements contained in the compound phase MC is preferably less than 1.0. If the atomic ratio of the light element amount is greater than this value, free carbon is easily generated in the alloy.

[0043] The particle size of the compound phase MC is preferably 0.1 to 6 μm. The particle size of the compound phase MC is the diameter of a circle having the same area as the cross-sectional area of ​​the compound phase MC in any cross section of the sintered alloy. In order to make the particle size of the compound phase MC less than 0.1 μm, it is necessary to make the raw material powder fine, which leads to increased costs and also deteriorates the moldability of the powder. If the particle size of the compound phase MC is greater than 6 μm, the mirror surface is reduced, and problems may occur if used in a metal mold. The particle size of the compound phase MC can be obtained by photographing the cross section of the sintered alloy with a scanning electron microscope (SEM) and using image analysis software based on the obtained SEM photograph. The particle size of the compound phase MC is more preferably 0.5 to 3 μm.

[0044] The particle size of the Cr3C2 phase is preferably 9 μm or less. If the particle size of the Cr3C2 phase is larger than 9 μm, the mirror surface may be reduced. The particle size of the Cr3C2 phase is obtained in the same manner as the particle size of the compound phase MC. The particle size of the Cr3C2 phase is more preferably 0.5 to 7 μm.

[0045] The sintered alloy of the present invention can be obtained by ordinary sintering, hot pressing sintering, etc. That is, a specified amount of powder is weighed, wet mixed, crushed, and dried, and then pressed by a metal mold to obtain a powder molded body. The powder molded body can be cut or ground to form a desired shape, or the powder molded body can be pre-sintered and then mechanically processed to obtain a specified shape. In addition, the powder can be filled into a metal mold of a specified shape and hot pressed to obtain a specified shape. In the case of ordinary sintering, the powder molded body is obtained by sintering the powder molded body at a sintering temperature of 1300 to 1500°C in a vacuum or in an atmosphere of an inert gas such as nitrogen or argon.

[0046] After sintering, HIP treatment can be further performed. The temperature of HIP treatment can be appropriately set according to the composition of the sintered alloy, but it can also be a temperature below the sintering temperature. This is because when the sintering temperature is higher than the sintering temperature, Cr carbides and the like will grow in grains, causing strength reduction. As a result, the pores generated during sintering can be reduced. Through HIP treatment, the grain size of the structure can also be adjusted.

[0047] A sintered alloy according to another embodiment of the present invention is characterized in that it includes a compound phase, a metal phase containing Ni, and a Cr3C2 phase, wherein the compound phase contains: one or more metal elements among Nb, Ta and Ti; and one or more of C and N, and has a NaCl type structure. By including the metal phase amount, the desired thermal expansion coefficient and toughness can be obtained. The content of the metal phase is preferably 8.2 volume % or less. By containing Ni as a metal phase, the sinterability can be improved, and the toughness can also be improved, but if the content of the metal phase is higher than 8.2 volume %, the surface roughness Ra after finishing becomes rough, and the resistance to tool deformation when used at high temperatures is reduced. The content of the metal phase is more preferably 8 volume % or less. In addition, the compound phase can be the same as the compound phase MC of the above-mentioned embodiment.

[0048] The metal phase may be composed of Ni alone, but Co and / or Fe may be used instead of Ni. In addition, Ni may be combined with Co and / or Fe. Ni improves the sinterability of the sintered alloy and also improves the oxidation resistance. Co and Fe increase the strength of the sintered alloy at room temperature and high temperature. In addition, Fe can be obtained at a relatively low cost. The content of each element may be selected in order to obtain the desired characteristics according to the use of the tool.

[0049] Regardless of the amount of metal phase, any method of common sintering and hot pressing sintering can be used. When using hot pressing sintering, the sintering temperature can be reduced. When the amount of metal phase is small and it is difficult to obtain a dense alloy by common sintering, sintering can also be performed by hot pressing. In this case, the content of the metal phase is preferably 0 to 0.5 volume %, more preferably 0 to 0.4 volume %. A sintered alloy that does not include a metal phase or contains a trace amount of a metal phase is formed by hot pressing, and while maintaining sinterability, the mirror surface can be further improved, and a sintered alloy suitable as a metal mold can be obtained.

[0050] Hot pressing is not particularly limited as long as it is a general method for forming a sintered alloy, but the sintering conditions are preferably carried out in a vacuum or in an inert gas atmosphere such as nitrogen or argon at a pressure of 20 to 100 MPa and a sintering temperature of 1200 to 1500° C. Alternatively, an apparatus other than hot pressing such as electric current sintering may be used.

[0051] The sintered alloy of the present invention can be used as a metal mold, especially a lens molding metal mold material, and is particularly suitable for use as a metal mold having a glass transition temperature Tg as low as less than 500°C and a thermal expansion coefficient of 15 to 25 MK. -1 The present invention is a metal mold for molding a chalcogenide glass lens. In addition, the present invention is applicable to the case where the metal mold for molding parts is required to have a thermal expansion coefficient greater than that of ordinary cemented carbide and binderless cemented carbide, or to the case where oxidation resistance is required, or to the case where a component or tool requiring a high thermal expansion coefficient, high wear resistance and excellent oxidation resistance is required.

[0052] [Example]

[0053] The present invention will be described in more detail with reference to Examples, but the present invention is not limited thereto.

[0054] The raw material powders used were Cr3C2 (2.2 μm), Ni (2.4 μm), Co (1.4 μm), Fe (3.0 μm), TaC (1.8 μm), NbC (1.6 μm), TiC (1.7 μm), Ti (C 0.5 ,N 0.5 )(2.3μm), TaN(2.1μm), Nb(C 0.7 N 0.3 )(2.5μm), WC(0.8μm), Mo2C(3.4μm) and various solid solution powders described in Table 1. The solid solution powders were prepared by blending carbides, nitrides and carbonitrides according to the composition shown in Table 1 and wet mixing. The mixed powders were solution treated in a high temperature furnace and crushed and screened to prepare raw material powders (1.3 to 3.1μm). The compound ratios constituting the compound phase MC described in Table 1 were calculated by converting the compound ratios during blending, the carbon content and the nitrogen content of the sintered alloy into each compound.

[0055] For samples containing a small amount of metal phase components, metal powder and other powders are pre-crushed by wet grinding. Samples containing more than 4% of metal phase components are used without pre-crushing. In addition, C powder is added for the purpose of reducing oxides contained in the powder and adjusting the carbon content according to the sample.

[0056] Sintering was performed by ordinary sintering in an inert gas atmosphere of nitrogen or argon, or by hot pressing sintering, and the obtained sintered body was subjected to HIP treatment to produce sintered alloys of inventions 1 to 32 and comparative products 1 to 2. In ordinary sintering, the sintering temperature was 1440°C, the pressure was 40 kPa, and the sintering atmosphere was N2 or Ar. In hot pressing sintering (inventive products 7, 8, 9, 10, 11, 13, 14, 29, 30, 31, comparative product 2), the sintering temperature was 1250°C, and the sintering atmosphere was Ar.

[0057]

Table 1-1

[0058]

[0059]

Table 1-2

[0060]

[0061] (Bending Strength)

[0062] The flexural strength (MPa) of the sintered alloys of Invention Products 1 to 32 and Comparative Products 1 and 2 was determined by flexural strength measurement (three-point bending test) according to the method of JIS B4104.

[0063] (Rockwell hardness)

[0064] The Rockwell hardness (HRA) of the sintered alloys of the invention products 1 to 32 and the comparative products 1 to 2 was measured by the Rockwell A hardness test method of the CIS027B sintered alloy.

[0065] (Coefficient of thermal expansion)

[0066] The sintered alloys of the inventions 1 to 32 and the comparatives 1 to 2 were heated from room temperature to 500°C and 800°C using a vertical thermal expansion instrument to measure the thermal expansion coefficients RT-500°C and RT-800°C, respectively (MK -1 ) measurement.

[0067] (Antioxidant)

[0068] The sintered alloys of the inventions 1 to 32 and the comparatives 1 to 2 were heated at 800°C and 1000°C for 30 minutes in the atmosphere, and the oxidation increments (oxidation weight per unit area) (g / m 2 ).

[0069] (Surface roughness after finishing)

[0070] The sintered alloys of Invention Products 1 to 32 and Comparative Products 1 to 2 were mirror-finished using diamond slurry, and the surface roughness Ra (nm) after processing was determined.

[0071] (evaluate)

[0072] A metal mold was prepared using the sintered alloys of Inventions 1 to 32 and Comparatives 1 to 2, and a chalcogenide glass lens was repeatedly molded. The metal mold was evaluated based on the number of repetitions and the mirror surface properties of the molded surface after repeated use.

[0073] Table 2 summarizes the properties of the sintered alloys of the inventions 1 to 32 and the comparatives 1 to 2. If the bending strength is above 700 MPa, there will be no problems in tool making and tool use. If the hardness is higher than 90.0 HRA, the tool life will not be shortened due to wear. If the thermal expansion coefficient (500°C) is 8 MK -1 The above allows the necessary alloy to be selected from the alloys of the present invention. The better the oxidation resistance, the longer the tool life, the smaller the surface roughness after finishing, and the better the quality of the formed material when used as a tool.

[0074]

Table 2

[0075]

[0076] The sintered alloys of inventions 1 to 32 have excellent oxidation resistance and mirror properties while maintaining the desired thermal expansion coefficient, and have excellent bending strength and hardness, and can also extend the life of the metal mold. In addition, invention 28 is a raw material powder of (W, Ta, Ti) C as the compound phase MC, which is a mixture of (W, Ti) C powder and TaC powder within the solid solubility limit in (W, Ti) C. Inventive product 15, because the content of the compound phase MC is small, 12% by volume, the Cr3C2 phase undergoes grain growth, and the strength is lower than that of other inventions, and a little cracking is observed. Inventive product 19, because the content of the compound phase MC is large, 40% by volume, the thermal expansion coefficient is small, and the demoulding property and mirror properties of the glass material are slightly inferior to those of other inventions. Inventive product 21, because the content of the metal phase is large, 9% by volume, the surface roughness Ra after finishing is rough, and the mirror properties are slightly inferior to those of other inventions. Comparative material 1 has poor oxidation resistance and cannot meet the prescribed usable times because the compound phase MC is composed of hexagonal WC. Comparative material 2 has poor oxidation resistance and cannot meet the prescribed usable times because the raw material powder of (W,Ti)C as the compound phase MC is a mixture of TiC powder and WC powder with a solubility higher than the solubility limit in TiC without solution treatment, so the WC phase as hexagonal crystals remains in the obtained sintered alloy, and has poor oxidation resistance and a small number of uses.

[0077] Inventions 5, 13, 22 and 25 have slightly poorer oxidation resistance than other inventions, but can be used repeatedly up to a predetermined number of times. Inventions 16 and 18 have excellent oxidation resistance and can maintain mirror properties even after being used repeatedly up to a predetermined number of times, and can continue to be used.

[0078] The cross section of the sintered alloy of Invention 18 was photographed using a scanning electron microscope (SEM). The obtained SEM photograph is shown in Figure 1 middle. Figure 1 The gray-black color in the SEM photo represents the Cr3C2 phase, and the gray-white color represents the compound phase MC. Figure 1 The particle sizes of the compound phase MC and the Cr3C2 phase were obtained by using the SEM photographs of the composite phase MC and the image analysis software (Image-Pro Plus manufactured by Media Cybernetics). The average particle size of the compound phase MC was 1.3 μm, and the average particle size of the Cr3C2 phase was 0.9 μm. The atomic ratio of the light element amount C contained in the compound phase MC to the amount of metal elements contained in the compound phase MC was 0.93.

Claims

1. A sintered alloy, characterized in that: It is composed of a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80% by volume has a NaCl type structure, wherein the solid solution phase contains: one or more metal elements selected from Nb, Ta and Ti; one or more of W and Mo; and one or more of C and N, wherein the sintered alloy contains 13 to 37% by volume of the compound phase, wherein 0.1 to 45 atomic% of one or more of W and Mo is solid-dissolved in the compound phase relative to the total amount of metal elements in the compound phase.

2. A sintered alloy, characterized in that: It is composed of a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80 volume % has a NaCl type structure, wherein the solid solution phase contains: metal elements of Ta and Nb and / or Ti; and one or more of C and N, and the sintered alloy contains 13 to 37 volume % of the compound phase.

3. A sintered alloy, characterized in that: It is composed of a compound phase and a Cr3C2 phase, wherein the compound phase contains: Ta; and one or more of C and N, and more than 80 volume % has a NaCl type structure, and the sintered alloy contains 13 to 37 volume % of the compound phase.

4. A sintered alloy, characterized in that: It is composed of a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80 volume % has a NaCl type structure, wherein the solid solution phase contains: metal elements of Nb and Ti; and one or more of C and N, and the sintered alloy contains 13 to 37 volume % of the compound phase.

5. A sintered alloy, characterized in that: The sintered alloy is composed of a compound phase and a Cr3C2 phase, wherein the compound phase contains: Nb; and C and N, and more than 80 volume % has a NaCl type structure, and the sintered alloy contains 13 to 37 volume % of the compound phase.

6. A sintered alloy, characterized in that: It is composed of a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase forms a solid solution phase, and more than 80% by volume has a NaCl type structure, the solid solution phase contains: one or more metal elements among Nb, Ta and Ti; one or more of W and Mo; and one or more of C and N, the metal phase contains one or more of Ni, Co and Fe, the sintered alloy contains less than 8.2% by volume of the metal phase, 13 to 37% by volume of the compound phase, and in the compound phase, 0.1 to 45 atomic % of one or more of W and Mo are solid-dissolved relative to the total amount of metal elements in the compound phase.

7. A sintered alloy, characterized in that: It is composed of a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase forms a solid solution phase, and more than 80 volume % has a NaCl type structure, the solid solution phase contains: metal elements of Ta and Nb and / or Ti; and one or more of C and N, the metal phase contains one or more of Ni, Co and Fe, and the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase.

8. A sintered alloy, characterized in that: It is composed of a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase contains Ta and one or more of C and N, and more than 80 volume % has a NaCl type structure, the metal phase contains one or more of Ni, Co and Fe, and the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase.

9. A sintered alloy, characterized in that: It is composed of a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase forms a solid solution phase, and more than 80 volume % has a NaCl type structure, the solid solution phase contains: metal elements of Nb and Ti; and one or more of C and N, the metal phase contains one or more of Ni, Co and Fe, and the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase.

10. A sintered alloy, characterized in that: It is composed of a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase contains Nb, C and N, and more than 80 volume % has a NaCl type structure, the metal phase contains one or more of Ni, Co and Fe, and the sintered alloy contains less than 8.2 volume % of the metal phase and 13 to 37 volume % of the compound phase.

11. The sintered alloy according to any one of claims 1 to 10, characterized in that: The particle size of the compound phase is 0.1 to 6 μm.

12. A metal mold formed of the sintered alloy according to any one of claims 1 to 10.

13. A method for manufacturing a sintered alloy, characterized in that: The invention relates to a method for manufacturing a sintered alloy, wherein the sintered alloy is composed of a compound phase and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80% by volume has a NaCl type structure, wherein the solid solution phase contains: one or more metal elements selected from Nb, Ta and Ti; and one or more selected from C and N. Containing 13 to 37% by volume of the compound phase, The raw material powder is molded and the obtained molded body is sintered by hot pressing.

14. A method for manufacturing a sintered alloy, characterized in that: The invention relates to a method for manufacturing a sintered alloy, wherein the sintered alloy is composed of a compound phase, a metal phase, and a Cr3C2 phase, wherein the compound phase forms a solid solution phase and more than 80% by volume has a NaCl type structure, wherein the solid solution phase contains: one or more metal elements selected from Nb, Ta, and Ti; and one or more selected from C and N, and wherein the metal phase contains one or more selected from Ni, Co, and Fe. Containing 13 to 37% by volume of the compound phase, The content of the metal phase is less than 0.5 volume %, The raw material powder is molded and the obtained molded body is sintered by hot pressing.

15. The method for producing a sintered alloy according to claim 13 or 14, characterized in that: The hot pressing is performed in a vacuum or in an inert gas atmosphere at a pressure of 20 to 100 MPa and a sintering temperature of 1200 to 1500°C.

Citation Information

Patent Citations

  • Collector for solar heat

    JP1982070357A

  • Image-forming device

    JP1985049978A

  • Method of making a cemented carbide

    CN104024447A